RETRACTED ARTICLE: Eco-reliable operation based on clean environmental condition for the grid-connected renewable energy hubs with heat pump and hydrogen, thermal and compressed air storage systems - Aboulbaba Eladeb; Ali Basem; Aman Sharma; Aashim Dhawan; Prabhat Sharma; Mohamed Bouzidi; Lioua Kolsi; Elnaz Naderi Drehshori (Scientific Reports)
Abstract Energy hubs, with their diverse regeneration and storage sources, can engage concurrently in energy transfer and storage. It is anticipated that managing the energy of these hubs within energy networks could enhance economic, environmental, and technical metrics. This article explains how electrical and thermal network hubs manage their energy consumption in the context of the multi-criteria objectives of efficiency, sustainability, reliability of the network operator, and operation. The hubs have solar power, a bio-waste unit, and wind turbines among other sustainable energy sources. They have compressed air, heat, and hydrogen storage units installed. Thermal energy is produced by means of a heat pump from electrical energy. Combining heat and power technology is used by both the bio-waste unit and the hydrogen storage unit. Subject to the operating model and reliability restrictions of these networks, the suggested strategy seeks to reduce the overall estimated costs of energy procurement, dependability, and emissions within the designated networks. Additional constraints of the problem encompass the operational model of sources and storages, conceptualized as an energy hub. This plan takes into account uncertainties about demand, energy costs, renewable energy sources, and the availability of network equipment. Reliability is accurately predicted by scenario-based techniques to stochastic optimization. The simultaneous modeling of economic, operational, reliability, and environmental indicators as well as the evaluation of the capabilities of heat pumps, biowaste units, compressed air and hydrogen storage units, and heat pumps in the hub performance are seen to be the new aspects of this approach. In summary, numerical results validate the usefulness of the proposed approach in enhancing the technical and financial aspects of thermal and electrical networks via efficient hub energy management. The incorporation of renewable hubs, equipped with storage units and heat pumps, has led to improvements in the economic, operational, reliability, and environmental conditions by approximately 44.1%, 28–90%, 85.6%, and 72.1% respectively, in comparison to load distribution studies.